Partial purification of histone H3 proteolytic activity from the budding yeast Saccharomyces cerevisiae. Issue 6 (7th April 2016) - Azad, Gajendra Kumar; Tomar, Raghuvir Singh
Abstract: The proteolytic clipping of histone tails has recently emerged as a novel form of irreversible post‐translational modification (PTM) of histones. Histone clipping has been implicated as a regulatory process leading to the permanent removal of PTMs from histone proteins. However, there is scarcity of literature that describes the identification and characterization of histone‐specific proteases. Here, we employed various biochemical methods to report histone H3‐specific proteolytic activity from budding yeast. Our results demonstrate that H3 proteolytic activity was associated with sepharose bead matrices and activity was not affected by a variety of stress conditions. We have also identified the existence of an unknown protein that acts as a physiological inhibitor of the H3‐clipping activity of yeast H3 protease. Moreover, through protease inhibition assays, we have also characterized yeast H3 protease as a serine protease. Interestingly, unlike glutamate dehydrogenase (GDH), yeast H3 proteolytic activity was not inhibited by Stefin B. Together, our findings suggest the existence of a novel H3 protease in yeast that is different from other reported histone H3 proteases. The presence of histone H3 proteolytic activity, along with the physiological inhibitor in yeast, suggests an interesting molecular mechanism that regulates the activity of histone proteases. Copyright © 2016 John Wiley & Sons, Ltd.